Ricardo Palma and Catholicism in the colonial baroque period - Salinas Barrón, Micaela Valeria (2021)
This article analyses Catholicism, which had a great influence on the colonial baroque period. To this end, we rely on the story «Entre jesuitas, agustinos y dominicos» (Between Jesuits, Augustinians and Dominicans). We will develop the theme of the actions of this institution, such as the application of exaggerated punishments, the role of the Jesuits, the abuse of their justified power and the satire in the stories of Ricardo Palma. The purpose of our text is to show the great manifestation that Palma carried out in the chosen story, evidencing through quotations the level of corruption, how the Jesuits were represented, the abuse of the church and in what way Palma employs the use of satire and makes it go hand in hand with the history.